2020
DOI: 10.1007/s40858-019-00318-8
|View full text |Cite
|
Sign up to set email alerts
|

Early production of reactive oxygen species coupled with an efficient antioxidant system play a role in potato resistance to late blight

Abstract: The association between reactive oxygen species (ROS) production and potato resistance to the hemibiotrophic pathogen Phytophthora infestans is poorly understood. In this study, the concentrations of hydrogen peroxide (H 2 O 2), malondialdehyde (MDA), and soluble phenolics, as well as the activities of superoxide dismutase, catalase, and ascorbate peroxidase were measured during the early biotrophic and late necrotrophic stages of P. infestans infection on resistant and susceptible 'Ovatio' and 'Bintje' potato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…For example El. Komy, M.H., Saleh showed that potato plants in response to a biotic stressor sharply increase the level of SOD activity in resistant varieties [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example El. Komy, M.H., Saleh showed that potato plants in response to a biotic stressor sharply increase the level of SOD activity in resistant varieties [26].…”
Section: Discussionmentioning
confidence: 99%
“…The change in POD activity is related to the defense system in the plant. The decline in POD activity at the beginning of the disease is due to the disruption of the metabolic balance in the plant by the pathogen, and the addition afterward is due to the production of large amounts of POD enzymes in the plant to remove the reactive oxygen damage caused by the pathogen [43,44]. In addition, the rate of changes in physicochemical values at different temperature conditions was not the same.…”
Section: Analysis Of the Changes In Physicochemical Valuesmentioning
confidence: 99%
“…The quick generation of ROS has been associated with the innate immunity of plants (Saeed andTrujillo 2022, Kobayashi et al 2012). Several ndings indicate that the resistance or susceptibility of late blight may be governed by the equilibrium between the activation of ROS/antioxidants (both in terms of intensity and timing) and the trophic stage of P. infestans (El_Komy et al 2020). To gain insights into the biochemical factors underlying tomato plant's response to R. s, it is crucial to investigate ROS generation, antioxidative mechanisms, and cell wall reinforcement in two distinct cultivars, Arka Meghali and BT-10, the results suggest that enhanced ROS production, along with an e cient antioxidative system, reduced lipid peroxidation rate, and increased lignin deposition in the cell wall, could play a key role in the resistance of tomato plants against R. s (Mandal, Das and Mishra 2011).…”
Section: Histological Effects Of R S Infection In Potato Plantsmentioning
confidence: 99%